Kompensasi Memediasi Beban Kerja Terhadap Kinerja Guru SMK Negeri 1 Bukateja - Efi Nur Farianti (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Performance improvement can be measured through fair workload and appropriate compensation, but the problem that occurs at SMK Negeri 1 Bukateja is the opposite. There are several teachers who receive excessive workload and inappropriate compensation, resulting in a decline in teacher performance. This study aims to analyze the mediating role of compensation in the relationship between workload and teacher performance, thereby increasing motivation and job satisfaction which will have an impact on teacher performance. This study is a quantitative study with data analysis techniques using Part Least Square (PLS-SEM) using SmartPLS 3.0 software. Sampling used a purposive sampling technique, namely 91 teachers, with a data collection method using a questionnaire. The results of the analysis of the research hypothesis show that workload has a positive and significant effect on the performance of SMK Negeri 1 Bukateja teachers, compensation has a positive and significant effect on workload of SMK Negeri 1 Bukateja, workload has a positive and significant effect on the performance of SMK Negeri 1 Bukateja teachers, and compensation can mediate workload on the performance of SMK Negeri 1 Bukateja teachers. The findings of this study indicate that fair and adequate compensation can reduce excessive workload on teacher performance at SMK Negeri 1 Bukateja. The R-Square result is 60.1%, which is in the moderate category, with the remaining 39.9% explained by other variables outside the study.